322 Unemployment at a young age and later unemployment in native Swedish and immigrant young adults. (11th October 2013) - Helgesson, M; Johansson, B J; Nordquist, T N; Lundberg, I L; Vingård, E V
Abstract : Objectives: The youth unemployment rate is increasing around the world due to recent recessions in the worldwide economy. Unemployment has been seen to affect future work participation. This register-based study examined the long-term effect of unemployment on future unemployment in Sweden. Methods: The study group of 199, 623 individuals included all immigrants born between 1968 and 1972 who immigrated to Sweden before 1990 (25, 607) and a random sample of native Swedes of the same age (174, 016). The follow-up period was 15 years, from 1993 to 2007. Results: Individuals who were unemployed in 1992 had an elevated risk of ≥100 days of unemployment during the whole follow-up period. The risk of unemployment in the follow-up increased with the length of unemployment in 1992. Immigrants had a higher risk of unemployment both at baseline and follow-up compared with native Swedes, but followed the same pattern as native Swedes when exposed to unemployment. For individuals with ≥100 days of unemployment in 1992, participation in an Active Labour Market Programme (ALMP) increased the risk of future unemployment, whereas both higher educational level at baseline and attainment of a higher educational level between 1992 and 1997 decreased the risk of future unemployment. Conclusion: Exposure to unemployment was associated with elevated risk of future unemployment 15 years after exposure. In addition to the human suffering caused, this can mean substantial costs in the form of increased welfare payments and loss of productivity and tax income to a society. ALMPs seem ineffective in promoting future work participation.